How to improve sleep in a neonatal intensive care unit: A systematic review. (October 2017) - van den Hoogen, Agnes; Teunis, Charlotte J.; Shellhaas, Renée A.; Pillen, Sigrid; Benders, Manon; Dudink, Jeroen
Abstract: There is increasing evidence that sleep plays a major role in the development of neural pathways in the neonatal brain. Several studies have suggested evidence-based approaches to improve sleep for infants admitted to the neonatal intensive care unit (NICU); however, in many neonatal centers very few of these strategies seem to be implemented in routine care. Objective: To systematically review the literature to determine interventions promoting neonatal sleep on the NICU, in order to develop key guidelines to improve neonatal sleep. Methods: A systematic search was conducted according to the criteria of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement for conducting and reporting systematic reviews. The search was performed in Pubmed, CINAHL and the Cochrane Library on 19 September 2016 and again on 28 January 2017. Results: In total, fourteen studies were included (10 RCT's and three quasi-experimental study designs): four studies were of high quality, eight of moderate quality and two of low quality. Two studies investigating kangaroo care reported significant effect on infant sleep behavior, two studies comparing Yakson and Gentle Human Touch (GHT) found significant effect on behavioral states and one study reported an increase in sleep behavior using different sleep surfaces. One study showed a significant effect on sleep patterns using music as an intervention and one study showed no significant effect using music. Two studies showed no significant effect on infant sleep using cycled light and different types of LED-light and one study showed significant effect of cycled lightning. There were no effects of Neonatal Individualized Developmental Care Program (NIDCAP) or massage therapy. Conclusion: Although many different interventions have been reported to promote sleep in infants who require intensive care, there is great heterogeneity across studies: the methods of sleep assessment, the targeted sleep behaviors, and the study populations vary significantly across published reports. Based on the results there seems to be insufficient evidence to recommend any new intervention to promote neonatal sleep on the NICU. However because of the importance of sleep for the development of the neonatal brain we do suggest some key guidelines based on moderate evidence, expert opinion and parental values to improve sleep on the NICU and to direct future neonatal sleep studies.